Kaleidoscope model of diabetes care: time for a rethink?. Issue 5 (May 2014) - Barnard, K. D.; Lloyd, C. E.; Dyson, P. A.; Davies, M. J.; O'Neil, S.; Naresh, K.; Lawton, J.; Ziegler, R.; Holt, R. I. G.
Abstract National Audit Data highlight persistent sub‐optimum control among increasing numbers of people living with diabetes, with severe consequences for the individual and the NHS. The aim of the present review was to introduce a new cohesive, holistic model of care, tailored to individual needs to support optimum diabetes outcomes. This model of diabetes is necessary in order to understand the driving forces behind behaviour and their impact on diabetes management. Feelings (an emotional state or reaction) and beliefs (an acceptance that something is true or real) are fundamental behavioural drivers and influence diabetes self‐management choices. Individually, these explain some of the complexities of behaviour and, collectively, they impact on personal motivation (rationale/desire to act) to achieve a specific outcome. Inevitably, they independently affect diabetes self‐management and the environment in which individuals live. A model of care that proposes the encompassing of environment, intrinsic thought and therapy regimens to provide tailored, personalized healthcare should support enhanced diabetes self‐management and outcomes from diagnosis. The Kaleidoscope model of care could be deliverable in routine care, incorporating each of the influences on diabetes self‐management, and should benefit both individuals with diabetes and healthcare professionals.